E-025 Transvenous embolization of cavernous carotid fistulas facilitated by a distal access catheter. (16th November 2010) - Haithcock, J; Toth, G; Pride, G
Abstract : Introduction and purpose: Although transvenous embolization of indirect carotid cavernous fistulas (iCCFs) represents an effective treatment strategy, venous navigation related limitations can prevent access to the entire fistulous site, decreasing the probability of definitive occlusion. In such cases, more invasive access to the involved vein, such as open surgical exposure, direct puncture of the superior ophthalmic vein or direct access to the anterior portion of the cavernous sinus may be needed to achieve a definitive cure. We describe two cases in which a coaxial technique using a commercially available distal access catheter facilitated venous navigation from the common femoral vein, enabling definitive obliteration of the iCCF. Our purpose includes reporting of these cases, discussion of endovascular strategies and a review of the various venous routes of access to the cavernous sinus. Materials and methods: We reviewed all recent endovascular procedures performed at our institution to identify two cases of iCCF in which a coaxial access technique using a commercially available distal access catheter was used to facilitate treatment. The procedural notes, hospital charts and imaging studies were reviewed to identify potential novel procedural details or problems related to this technique. Additionally, we reviewed the current medical literature related to endovascular iCCF embolization in order to complement our summary review of the various venous approaches employed for iCCF treatment. Results: The coaxial technique using a distal access catheter to achieve fistula access from the common femoral vein facilitated complete iCCF obliteration in both of our cases, without any added periprocedural morbidity. The technique was straightforward, easily applied and greatly simplified transvenous embolization of the iCCF in both cases. Conclusion: The distal access catheter was introduced as an adjunct device for mechanical thrombectomy procedures using the Merci embolectomy system by providing microcatheter support during clot retrieval and improved stability in tortuous arterial anatomy. Similarly, successful endovascular treatment of iCCFs from a transvenous approach also requires navigation through tortuous venous anatomy and enhanced microcatheter stability in order to achieve successful embolization of the fistula. A distal access catheter was used in two patients with iCCFs treated via a transvenous endovascular approach which greatly facilitated complete obliteration of the fistula in both cases. The use of a distal access catheter in mechanical thrombectomy procedures is well documented, and given the ease of use and compatibility with the various guiding catheters and microcatheters currently available, the distal access catheter will likely have an increasing role in other intracranial neurointerventional procedures.